Classroom-Level Positive Behavior Supports in Schools Implementing SW-PBIS: Identifying Areas for Enhancement. (January 2013) - Reinke, Wendy M.; Herman, Keith C.; Stormont, Melissa
This study evaluated the use of classroom-level behavior management strategies that align with School-Wide Positive Behavioral Interventions and Supports (SW-PBIS). Direct observations of universal classroom management strategies were conducted across 33 elementary classrooms in elementary schools implementing SW-PBIS with high fidelity. Findings indicate that classrooms had posted positively stated classroom rules at high rates, whereas teacher use of specific praise and the ratio of positive to negative interactions were less than optimal. Furthermore, classroom teachers with higher rates of general praise were found to report being more efficacious with regard to classroom management. In turn, teachers in classrooms with higher rates of disruptive behavior reported feeling less efficacious. In addition, teachers with lower rates of positive to negative interaction, who used higher rates of harsh reprimands and had higher rates of disruptions, reported higher levels of emotional exhaustion. Implications for developing supports to assist teachers struggling with universal classroom management strategies are described.